Clinically relevant differences in COPD health status: systematic review and triangulation. Issue 3 (6th September 2018) - Alma, Harma; de Jong, Corina; Tsiligianni, Ioanna; Sanderman, Robbert; Kocks, Janwillem; van der Molen, Thys
The minimal clinically important difference (MCID) quantifies when measured differences can be considered clinically relevant. This study aims to review and triangulate MCIDs of chronic obstructive pulmonary disease (COPD) health status tools. A systematic search in PubMed, EMBASE and Cochrane Library was conducted (Prospero #CRD42015023221). Study details, patient characteristics, MCID methodology and estimates were assessed and extracted by two authors. A triangulated mean was obtained for each tool's MCID, with two-thirds weighting for anchor-based and one-third for distribution-based results. This was then multiplied by a weighted factor based upon the study size and quality rating. Overall, 785 records were reviewed of which 21 studies were included for analysis. MCIDs of 12 tools were presented. General quality and risk of bias were average to good. Triangulated MCIDs for the COPD Assessment Test (CAT), Clinical COPD Questionnaire (CCQ) and St. George's Respiratory Questionnaire (SGRQ) were −2.54, −0.43 and −7.43 for improvement. Too few and/or too diverse studies were present to triangulate MCIDs of other tools. Evidence for the MCID of the CAT and CCQ was strong and triangulation was valid. Currently used MCIDs in clinical practice for the SGRQ (4) and Chronic Respiratory Questionnaire (0.5) did not match the reviewed content, for which the MCIDs were much higher. Using too low MCIDs may lead to an overestimation of the interpretation of treatment effects. MCIDs for deterioration were scarce, which highlights the need for more research. Reviewed and triangulated thresholds for minimal clinically relevant improvements are −2.54 (CAT), −0.43 (CCQ) and −7.43 (SGRQ) http://ow.ly/1y4v30l1yVI